Emerging Field Grading Spacer Magnetron Sputtered with a CCTO Layer for DC GIL/GIS - Jin Li; Yufan Wang; Mi Xiao; Hucheng Liang; Hang Yao; Boxue Du (CSEE Journal of Power and Energy Systems)
Insulation failures of epoxy spacers applied in gas insulated transmission line/switchgear (GIL/GIS) often occur, primarily due to electric field distortion. In this paper, a field graded coating CaCu3Ti4012 (CCTO) is presented to enhance the flashover performance of a GIL/GIS spacer. First, CCTO layers of different thicknesses are deposited on the spacer surface using magnetron sputtering technology. Then, insulating properties of these sputtered spacers under alternating current, direct current, and polarity reversal (PR) voltages and with the existence of metal particles are researched by experimental and simulation methods. Results show the short-term (30 and 60 min) sputtering treatments have no obvious effect on improving insulating properties.